2024
DOI: 10.1101/2024.06.06.597807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular and spatial transcriptomic classification of midbrain dopamine neurons and their alterations in a LRRK2G2019Smodel of Parkinson’s disease

Zachary Gaertner,
Cameron Oram,
Amanda Schneeweis
et al.

Abstract: Several studies have revealed that midbrain dopamine (DA) neurons, even within a single neuroanatomical area, display heterogeneous properties. In parallel, studies using single cell profiling techniques have begun to cluster DA neurons into subtypes based on their molecular signatures. Recent work has shown that molecularly defined DA subtypes within the substantia nigra (SNc) display distinctive anatomic and functional properties, and differential vulnerability in Parkinson’s disease (PD). Based on these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 107 publications
0
0
0
Order By: Relevance
“…In contrast, co-release of GABA from DA neurons is less well understood. Though there seem to be small subsets of DA neurons expressing GAD1/2 (Azcorra et al, 2023;Gaertner et al, 2024) and even VGAT (Conrad et al, 2024) the majority does not. Rather, it was suggested that GABA is taken up from outside by the plasmalemmal GABA transporter GAT1 (Melani et al, 2022;Tritsch et al, 2014) and/or synthesized de novo by ALDH1a1 (Kim et al, 2015) prior to being loaded into vesicles by VMAT2 (Melani et al, 2022;Tritsch et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, co-release of GABA from DA neurons is less well understood. Though there seem to be small subsets of DA neurons expressing GAD1/2 (Azcorra et al, 2023;Gaertner et al, 2024) and even VGAT (Conrad et al, 2024) the majority does not. Rather, it was suggested that GABA is taken up from outside by the plasmalemmal GABA transporter GAT1 (Melani et al, 2022;Tritsch et al, 2014) and/or synthesized de novo by ALDH1a1 (Kim et al, 2015) prior to being loaded into vesicles by VMAT2 (Melani et al, 2022;Tritsch et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…This finding was rather surprising because GABA is a zwitterionic amino acid and structurally very different from classical VMAT2 substrates that have an aromatic ring and a positive charge (Peter et al, 1994;Yelin et al, 1995;Zheng et al, 2006). In contrast to glutamate, which is presumably present in all cells with active gene expression, GABA is typically produced through decarboxylation of glutamate in cells containing GAD1 or GAD2, which are little expressed in DA neurons (Azcorra et al, 2023;Gaertner et al, 2024;Tritsch et al, 2014). But how do DA neurons get GABA in the first place?…”
Section: Introductionmentioning
confidence: 99%